Pengaruh Laporan Segmen Terhadap Keputusan Investor - Yuniarwati, Elizabeth Sugiarto Dermawan, Melinda Haryanto, (Jurnal Akuntansi, 2014)
This Study Investigates The Reaction Of Investors To The Segment Disclosures Presented In The Financial Statement Using Data Classification Condition: Full Sample Data, Non Traceable Income Data That Has Negative Income.